Design and Commissioning of a Three-Barrel Shattered Pellet Injector for DIII-D Disruption Mitigation Studies. (3rd October 2017) - Meitner, S.; Baylor, L. R.; Commaux, N.; Shiraki, D.; Combs, S.; Bjorholm, T.; Ha, T.; McGinnis, W.
Abstract: Disruptions are sudden unplanned terminations of tokamak plasmas that can lead to high thermal loads and runaway electrons (REs). Unmitigated disruptions in ITER are predicted to dissipate up to 350 MJ of thermal energy and generate several MA of multi-MeV runaway electrons. This intense heat and energetic particle beams can cause localized melting of the plasma facing components. Reliable and fast acting disruption mitigation (DM) techniques are therefore a critical requirement for ITER to safeguard the machine from damage. The proven method for DM centers on injecting a large quantity of impurity particles into the plasma to quickly increase density and radiate the thermal energy to mitigate thermal effects. Additionally, if the particle injection can achieve sufficient density, it can create collisional drag which suppresses the formation of REs. Shattered pellet injection (SPI) has proven to be the most effective method of particle injection thus far attempted and is planned for the DM system on ITER. Recently, a new three-barrel second SPI (SPI-II) system has been developed for use on DIII-D to study injection effects from multiple toroidal locations and pellet timing. The three pellets can be formed and fired individually or simultaneously. The SPI-II has provisions for making and firing pure species pellets with deuterium, neon, or argon and also deuterium layered pellets with a core of neon and mixtures of neon and deuterium.